2015
DOI: 10.1007/s11883-015-0491-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a genetic disorder characterized by elevated low-density lipoprotein (LDL) cholesterol and premature cardiovascular disease, with a prevalence of approximately 1 in 200-500 for heterozygotes in North America and Europe. Monogenic FH is largely attributed to mutations in the LDLR, APOB, and PCSK9 genes. Differential diagnosis is critical to distinguish FH from conditions with phenotypically similar presentations to ensure appropriate therapeutic management and genetic couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
17

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 126 publications
0
59
0
17
Order By: Relevance
“…40,41 Therefore, it may be beneficial to undertake sequencing of the entire APOB gene because other rare variants in the gene may be responsible for the patient's clinical phenotype. 36,39 In the present study, we screened the whole exons in APOB and found some mutations in nonhot region. The hot exon of 26 showed a frequency of 37.8% in APOB mutations.…”
Section: Et Al Familial Hypercholesterolemia In China 577mentioning
confidence: 96%
See 1 more Smart Citation
“…40,41 Therefore, it may be beneficial to undertake sequencing of the entire APOB gene because other rare variants in the gene may be responsible for the patient's clinical phenotype. 36,39 In the present study, we screened the whole exons in APOB and found some mutations in nonhot region. The hot exon of 26 showed a frequency of 37.8% in APOB mutations.…”
Section: Et Al Familial Hypercholesterolemia In China 577mentioning
confidence: 96%
“…34,38 The elevated prevalence of APOB mutations among Chinese patients might be possible, as pointed out by Andersen et al 38 Additionally, most currently available genetic testing in APOB is focused on exon 26 and p.Arg3500Trp rather than on the entire coding region. 39 Of note, there are case studies reporting mutations in the non-hot spot of APOB. 40,41 Therefore, it may be beneficial to undertake sequencing of the entire APOB gene because other rare variants in the gene may be responsible for the patient's clinical phenotype.…”
Section: Et Al Familial Hypercholesterolemia In China 577mentioning
confidence: 99%
“…Overly narrow criteria may limit the review to a tiny subgroup of the affected patient population. For example, a review of the use of high‐dose omega‐3 fatty acid supplementation to prevent a second myocardial infarction in men aged 80 years or older with a history of prostate cancer and familial hypercholesterolemia would likely produce few studies and information useful for only a few patients because the prevalence of familial hypercholesterolemia is only about 0.2–0.5%, and the search criteria would produce a small subset of that group . Conversely, overly broad criteria may render the review results clinically meaningless.…”
Section: Methodsmentioning
confidence: 99%
“…These polygenic influences alone (without any pathogenic mutation found in the classic 3 genes) can account for levels corresponding to homozygous FH (above 500 mg/dL) 80) . It has become clear that the genetics determining LDL-c levels is far more complex than originally believed with additional genes still being pursued 81) . As such, failure to detect a mutation does not exclude a diagnosis of FH, particularly if the clinical phenotype is highly suggestive of FH 76,78,82) .…”
Section: Hybrid Modelmentioning
confidence: 99%